2007
DOI: 10.1111/j.1468-0262.2007.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Neighborhood Effects

Abstract: Families, primarily female-headed minority households with children, living in highpoverty public housing projects in five U.S. cities were offered housing vouchers by lottery in the Moving to Opportunity program. Four to seven years after random assignment, families offered vouchers lived in safer neighborhoods that had lower poverty rates than those of the control group not offered vouchers. We find no significant overall effects of this intervention on adult economic self-sufficiency or physical health. Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
878
2
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,051 publications
(917 citation statements)
references
References 48 publications
28
878
2
9
Order By: Relevance
“…The MTO research design randomly assigns public housing residents who volunteer to participate to one of three experimental groups: (1) controls that get no voucher but can stay in public housing in disadvantaged neighborhoods; (2) recipients of rental vouchers; and (3) recipients of rental vouchers and relocation assistance who had to move to neighborhoods with , 10 per cent poverty rates and remain for at least a year. Most investigations of MTO data uncovered no substantial neighborhood effects on adult labor market outcomes (e.g., Goering & Feins, 2003;Katz et al, 2001;Kling et al, 2007;Ludwig, 2012;Ludwig et al, 2000Ludwig et al, , 2001aLudwig et al, , 2001bLudwig et al, , 2008Orr et al, 2003;Sanbonmatsu et al, 2011). Moreover, MTO-based studies indicated small or insignificant neighborhood effects on youth educational outcomes (Kling et al, 2007;Ludwig et al, 2001b;Sanbonmatsu et al, 2011).…”
Section: Random Assignment Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…The MTO research design randomly assigns public housing residents who volunteer to participate to one of three experimental groups: (1) controls that get no voucher but can stay in public housing in disadvantaged neighborhoods; (2) recipients of rental vouchers; and (3) recipients of rental vouchers and relocation assistance who had to move to neighborhoods with , 10 per cent poverty rates and remain for at least a year. Most investigations of MTO data uncovered no substantial neighborhood effects on adult labor market outcomes (e.g., Goering & Feins, 2003;Katz et al, 2001;Kling et al, 2007;Ludwig, 2012;Ludwig et al, 2000Ludwig et al, , 2001aLudwig et al, , 2001bLudwig et al, , 2008Orr et al, 2003;Sanbonmatsu et al, 2011). Moreover, MTO-based studies indicated small or insignificant neighborhood effects on youth educational outcomes (Kling et al, 2007;Ludwig et al, 2001b;Sanbonmatsu et al, 2011).…”
Section: Random Assignment Experimentsmentioning
confidence: 96%
“…Most investigations of MTO data uncovered no substantial neighborhood effects on adult labor market outcomes (e.g., Goering & Feins, 2003;Katz et al, 2001;Kling et al, 2007;Ludwig, 2012;Ludwig et al, 2000Ludwig et al, , 2001aLudwig et al, , 2001bLudwig et al, , 2008Orr et al, 2003;Sanbonmatsu et al, 2011). Moreover, MTO-based studies indicated small or insignificant neighborhood effects on youth educational outcomes (Kling et al, 2007;Ludwig et al, 2001b;Sanbonmatsu et al, 2011). 7 Sweeping negative conclusions are inappropriate given the substantial shortcomings of MTO as a test of neighborhood effects (cf.…”
Section: Random Assignment Experimentsmentioning
confidence: 96%
“…In particular, for each study, we generate a mean effect across all available outcomes (following Kling and Liebman 2004;Kling, Liebman, and Katz 2007) where the indices are calculated from the standardized outcome measures of each study.…”
Section: ) Knowledge Of and Interest In Politicsmentioning
confidence: 99%
“…First, observational data suggest that neighborhood poverty is associated with the inconsistency of maternal parenting practices within the home (5,6), and the strongest findings based on a randomized voucher experiment in the Moving to Opportunity (MTO) program (7) show that moving to neighborhoods with relatively low poverty rates has a substantial positive impact on caregivers' mental health. Hence, there are plausible theoretical reasons to hypothesize that neighborhood disadvantage constrains parental practices and the family environment ''under the roof'' (8), which may in turn bear on cognitive achievement.…”
mentioning
confidence: 99%